An Application of The Markowitz’s Mean-Variance Framework in Constructing Optimal Portfolios using the Johannesburg Securities Exchange Tradeable Indices: Array - Huni, Sally; Sibindi, Athenia Bongani (The Journal of Accounting and Management, 2020)
The aim of this study was to assess the feasibility of constructing optimal portfolios using the Johannesburg Securities Exchange (JSE) tradable sector indices. Three indices were employed, namely Financials, Industrials and Resources and these were benchmarked against the JSE All Share Index for the period January 2007 to December 2017. The period was split into three, namely before the 2007-2009 global financial crises, during the global financial crises and after the global financial crises. The Markowitz’s mean-variance optimisation framework was employed for the construction of global mean variance portfolios. The results of this study demonstrated that it was feasible to construct mean-variance efficient portfolios using the tradable sector indices from the JSE. It was also established that, on the other hand, global mean variance portfolios constructed in this study, outperformed the benchmark index in a bullish market in terms of the risk-return combinations. On the other hand, in bear markets, the global mean variance portfolios were observed to perform better than the benchmark index in terms of risk. Further, the results of the study showed that portfolios constructed from the three tradable indices yielded diversification benefits despite their positive correlation with each other. The results of the study corroborate the findings by other scholars that the mean-variance optimisation framework is effective in the construction of optimal portfolios using the Johannesburg Securities Exchange. The study also demonstrated that Markowitz’s mean-variance framework could be applied by investors faced with a plethora of investment constraints and choices to construct efficient portfolios utilising the JSE tradable sector indices in order to realise returns commensurate with their risk preferences.